Simulation of an indium gallium nitride quantum well light-emitting diode with the non-equilibrium Green's function method - Shedbalkar, Akshay; Andreev, Zhelio; Witzigmann, Bernd (physica status solidi (b), 2016)
This work presents a quantum mechanical simulation of an indium gallium nitride (InGaN) based light-emitting diode (LED) using the non-equilibrium Green's function (NEGF) method. Due to the wurtzite crystal structure, such LEDs exhibit strong polarization-induced electric fields at heterointerfaces. Standard simulation methods based on the drift-diffusion (DD) model do not take into account potentially important transport mechanisms such as quantum mechanical tunneling or non-equilibrium carrier distributions in the device. These effects are included in the NEGF model, while the semi-classical models employ parametrized approximations. In principle, the NEGF simulation therefore allows a more realistic view of the physical process that take place in the LEDs.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Contacts; GaN; Light-emitting diodes; Minority carriers; Non-equilibrium Green's function method; Optoelectronics